Matrix Metalloproteinase-1 and Acid Phosphatase in the Degradation of the Lamina Propria of Eruptive Pathway of Rat Molars - Pizzol Junior, Jose Paulo de; Sasso-Cerri, Estela [UNESP]; Cerri, Paulo Sergio [UNESP] (Mdpi, 2018)
The comprehension of dental pathogenesis and disorders derived from eruption failure requires a deep understanding of the molecular mechanisms underlying normal tooth eruption. As intense remodelling is needed during tooth eruption, we hypothesize that matrix metalloproteinase-1 (MMP-1) and acid phosphatase (ACP) play a role in the eruptive pathway degradation. We evaluated MMP-1-immunoexpression and the collagen content in the lamina propria at different eruptive phases. Immunohistochemistry and ultrastructural cytochemistry for detection of ACP were also performed. In the maxillary sections containing first molars of 9-, 11-, 13-, and 16-day-old rats, the birefringent collagen of eruptive pathway was quantified. MMP-1 and ACP-2 immunohistochemical reactions were performed and the number of MMP-1-immunolabelled cells was computed. Data were analyzed by one-way ANOVA and Tukey post-test (p <= 0.05). ACP cytochemistry was evaluated in specimens incubated in sodium beta-glycerophosphate. In the eruptive pathway of 13- and 16-day-old rats, the number of MMP-1-immunolabelled cells increased concomitantly to reduction of collagen in the lamina propria. Enhanced ACP-2-immunolabelling was observed in the lamina propria of 13- and 16-day-old rats. Fibroblasts and macrophages showed lysosomes and vacuoles containing fragmented material reactive to ACP. MMP-1 degrades extracellular matrix, including collagen fibers, being responsible for the reduction in the collagen content during tooth eruption. The enhanced ACP activity at the mucosal penetration stage indicates that this enzyme plays a role in the degradation of remnant material, which is engulfed by macrophages and fibroblasts of the eruptive pathway. Therefore, enzymatic failure in the eruptive pathway may disturbs tooth eruption.
Keywords: eruptive pathway; matrix metalloproteinase-1; acid phosphatase; ultrastructure; lamina propria; birefringent collagen